2022
DOI: 10.1002/andp.202200130
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Manipulations with VO2‐Doped Dielectric Electromagnetically Induced Transparency and Absorption

Abstract: Superior analogs for electromagnetically induced transparency (EIT) and absorption (EIA) in metasurfaces (MSS) are universal, but fewer integrate both effects in one device, let alone contribute to polarization manipulations. Here, note that asymmetrical EITs are rigorously demonstrated under both polarization incidences in dielectric orthogonal dumbbell‐shaped structures, with a maximum group delay of 335 ps. The transverse magnetic (TM) mode excited EIT holds a transparent window at 1.318 THz close to the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…A strong coupling between the NR and free space leads to a large radiation loss, resulting in a wide spectrum and a tiny Q value (quality factor Q = f /Δ f , where f stands for the resonant frequency and Δ f presents the half peak bandwidth) of 19.7 within the transmission spectrum. 47 In contrast, in Fig. 6(b), the transmission dip of 0.141 at 2.318 THz can be achieved by exciting the CS with the incident EM waves.…”
Section: Design Process and Discussionmentioning
confidence: 94%
“…A strong coupling between the NR and free space leads to a large radiation loss, resulting in a wide spectrum and a tiny Q value (quality factor Q = f /Δ f , where f stands for the resonant frequency and Δ f presents the half peak bandwidth) of 19.7 within the transmission spectrum. 47 In contrast, in Fig. 6(b), the transmission dip of 0.141 at 2.318 THz can be achieved by exciting the CS with the incident EM waves.…”
Section: Design Process and Discussionmentioning
confidence: 94%
“…Placed above the four C-shaped dielectric rings (dark plasmon resonators), the Ge CRP exhibits a metallic state under illumination and the near-field coupling with the dark plasmon resonators enhances the loss of the dark plasmon resonators. [44] Related experiments have shown that the coupling between attenuated radiation and dark modes can ef-fectively transition the PIT to EIA, and this has been verified in the radiation spring oscillator model, [34] which is homologous to either the generation of magnetic dipoles or the introduction of coupled phase detuning. Therefore, the introduction of the GMST species CRP proposed in this paper produces a phase constructive interference that eliminates the residual effect of the remaining phase destructive interference at the frequency point near the narrowband EIA and further enhances the broadband effect of the original absorption window, (indirectly attenuated phase destructive interference).…”
Section: Mechanistic Analysis Of Broadband Eiamentioning
confidence: 87%
“…In this case, there is a strong coupling with free space, and at the same time, there is a large radiation loss, which is manifested in the transmission spectrum as a wide spectrum and a small Q value of 10.7 (quality factor Q = f /Δf for the fundamental resonant mode, f is the resonant frequency and Δf denotes the halfpeak bandwidth). [44] As can be seen from Figure 3c,d, the two C-shaped dielectric rings with the notch linkage direction along the electric field direction can be directly excited by the incident electric field due to the asymmetry of the structure. The remaining two C-shaped dielectric rings are almost unresponsive and can only be excited indirectly, showing the magnetic dipole property, which is Mie resonance.…”
Section: Pit Mechanism Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…From the above research results, the performance of terahertz polarization converters in terms of polarization conversion bandwidth, PCR, and RBW needs to be further improved. To solve these problems, a polarization conversion device based on the Fabry-Pérot (F-P) cavity model is designed, , in which each layer is equivalent to a mirror, and the interference of polarization couplings in a multireflection process may either enhance or reduce the overall emergent fields with co- and cross-polarization. Moreover, the performance of terahertz metasurface polarization converters could not be tunable or switchable after the design is completed, which greatly limits their application range and flexibility.…”
Section: Introductionmentioning
confidence: 99%